(untitled) (Journal of Human Sciences, 2025)
William James, in his pragmatic philosophy, addresses a key point concerning the definition of meaning. James emphasizes that a statement has meaning only if it leads to practical and achievable results. Ideas that cannot be transformed into sensory experiences are considered meaningless, and anyone who perceives them otherwise is deluded. James also introduced the "theory of truth," which suggests that ideas are not necessarily true but gain their value from their practical utility and immediate impact. James opposes monism and prefers the vast diversity in the universe, highlighting the balance between actual experience and spiritual aspirations. He argues that truths are mutable and not fixed, leading him to criticize both materialist and idealist philosophies. The former eradicates the spiritual aspect of humanity, while the latter disregards what is tangible and partial. James embraced pragmatism because it allows a balance between realistic experiences and spiritual beliefs, using practical results as a criterion for determining the value of ideas. He believes that philosophers should follow this approach because it acknowledges the principles of science and actual experience, making it a reaction against idealist and metaphysical doctrines that surpass reality. Based on this, the study discusses pragmatism in William James’ philosophy. The first section addresses the linguistic and terminological meaning of pragmatism, highlighting its main types and philosophical and scientific origins. The second section analyzes and studies pragmatism in James’ work and the foundations of his philosophy. The study concludes that the term "pragmatism" is a borrowed term, derived from Greek. The aim of the founder of the pragmatic method, Charles Peirce, was to introduce something new, thus creating a new term from another language